AB1059 The prevalence of dense fine speckled pattern in routine screening for systemic autoimmune diseases using indirect immunofluorescence-antinuclear antibody test. (15th June 2017) - Kim, S; Jeon, YL; Kim, MH; Lee, WI; Kang, SY
Abstract : Background: The nuclear dense fine speckled (DFS) pattern is one of the most commonly observed finding in indirect immunofluorescence-antinuclear antibody (IIF-ANA) assay on HEp-2 cells. Unlike other ANA, DFS pattern is not prevalent in ANA-associated rheumatic diseases (AARD). The antigen was initially named DFS70 (70kD protein) according to the IIF pattern and later known as the lens epithelium-derived growth factor p75 (LEDGF/p75). Autoantibodies showing a DFS pattern have been reported in interstitial cystitis, various chronic inflammatory conditions, autoimmune thyroiditis, atopic dermatitis, cancer, as well as in apparently healthy individuals. Among IIF-ANA tests referred to the laboratory from the Department of Dermatology, the most common IIF-ANA positive pattern is DFS. Objectives: To compare the clinical significance of DFS pattern in dermatologic diseases (including alopecia) with other departments. Methods: Between June and December 2016, IIF-ANA testing using HEp-2 cell line slide (Kallestad; Bio-Rad, USA) was performed on 4, 130 samples referred as screening for systemic autoimmune diseases in Kyung Hee University Hospital. The identified patterns in IIF-ANA assays were analyzed according clinical department and diagnosis. Results: The Department of Dermatology was the most requesting IIF-ANA assay (2579/4130, 62.4%) and the Department of Rheumatology and the remaining departments were 18.1% (749/4130) and 19.5% (802/4130), respectively. The prevalence of IIF-ANA positivity was 10.97% (453/4130) and those of the Department of Dermatology, the Department of Rheumatology, and the remaining departments were 8.5% (219/2579), 15.5% (116/749), and 14.7% (118/802), respectively. The DFS pattern was the most common IIF-ANA positive pattern (173/453, 38.2%) and the prevalence of DFS pattern in the Department of Dermatology, the Department of Rheumatology, and the remaining departments were 48.4% (106/219), 26.7% (31/116), and 30.5% (36/118), respectively. Among 173 patients with ANA pattern of DFS, 168 patients were reviewed based on their medical chart. The most of patients were from Department of Dermatology and Rheumatology. 101 patients with positive DFS were from Department of Dermatology, the majority of 55 patients were diagnosed with alopecia. 31 patients of department of Rheumatology showed positive ANA pattern of DFS and a great part of patients were diagnosed with rheumatism. Conclusions: According to previous studies, up to 20% of healthy individuals have been reported to have a positive IIF-ANA test and the DFS pattern has been reported in 33% of ANA positive healthy individuals, but not in ANA positive systemic autoimmune diseases. In this study the prevalence of DFS pattern of ANA positivity in patients with dermatologic diseases including alopecia was similar with prevalence reported in healthy individuals. The patients with alopecia appear to show higher prevalence of positive ANA pattern of DFS than other patients with dermatologic disorders. This study was performed with routinely IIF-ANA requested patients to screen for systemic autoimmune diseases. Therefore, further evaluations comparing healthy individuals and patient group with more various disease entities are needed to confirm our findings. Disclosure of Interest: None declared